Addition of Sodium Chlorine on culture of Dunaliella tertiolecta ATCC 30929 :Implication on Intracellular Lipid Content - Karseno Karseno; Matsumi Takagi; Toshiomi Yoshida (Indonesian Food and Nutrition Progress, 2003)
The effect of addition sodium chloride (NaC1) on the accumulation intracellular of lipid in Dunaliella cells was investigated. Although initial NaC1 concentration higher than 1.5 M markedly inhibited cell growth, increase of initial NaCI concentration from 0.5 (eq. to sea water) to 1.0 M resulted in a higher intracellular lipid content (67%) in comparison with 60% for the salt concentration of 0.5 M Addition of 0.5 or 1.0 M NaC1 at mid-log phase or the end of log phase during culture with initial NaC1 concentration of 1.0 M further increased the lipid content (70%). Addition of 2.0 M NaC1 decreased final cell concentration to almost half of that without addition, although it resulted in very high lipid content of 77%.